The Influence of Community Participation and Organizational Culture on Tourism Development in Padang Lawas Regency - M. Rasyidi Hasibuan; Ali Mukti Tanjung; Didin Muhafidin (The Future of Education Journal, 2025)
This study aims to determine the influence of community participation and organizational culture on tourism development in Padang Lawas Regency. The research method used is quantitative, with a sample size of 80 people. Data collection methods include literature review, interviews, questionnaires, and documentation. Data analysis was conducted to test the hypotheses using correlation analysis with SPSS. The results of the study show that the community participation factors examined, including as a goal (objective), as a legally valid action (authoritative choice), and as a hypothesis, have a positive and significant effect on tourism development in Padang Lawas Regency. The analysis shows that community participation influences tourism development by 0.406 with significance at the 0.000 level, indicating a positive and significant contribution of community participation to tourism development. Therefore, the hypothesis stating that the influence of community participation on tourism development is determined by dimensions of community participation, which include decision-making, program implementation, monitoring and evaluation, and the utilization of results, is proven to have a positive and significant effect on tourism development, contributing 40.6%. Similarly, organizational culture, which encompasses academic culture, socio-cultural aspects, and democratic practices, also shows a positive and significant contribution to tourism development with a beta value of 0.427. This indicates a positive and significant contribution of organizational culture to tourism development. Overall, community participation and organizational culture contribute positively and significantly by 58.2% to tourism development, while the remaining 41.8% is influenced by other variables not examined in this study.